Análise de desempenho de motor diesel com injeção eletrônica Common Rail alimentado com misturas diesel - biodiesel em dinamômetro de chassis - Podorodeczki, Paulo Ricardo (2016)
The present work analyzes the performance and consumption of an electronically managed diesel cycle engine using the Common Rail system equipping a utility vehicle, varying the volume of Biodiesel added to the diesel. The S10 diesel fuel purchased at gas stations, consisting of 7% of Biodiesel already in its composition, and adding Biodiesel in volume of 5 in 5% up to pure Biodiesel (100%) was used for the tests. The tests were carried out on a roller dynamometer in order to obtain and analyze data of torque, power and specific consumption, in order to obtain data for further analysis and make comparisons with previously published theoretical reference. The results showed that there is a better performance range between 10% and 30% where there is a 3% increase in performance with the lowest specific consumption and with the gradual increase of the percentage of Biodiesel, the performance declines of the order of 11, 8% in the maximum torque and 8.2% in the power generated by the engine to 100% Biodiesel, being this one that presented the worst performance.